A Comparitive Study Of The Social Science Achievements Of Secondary School Students With Respect To Gender And Ownership Of The School Hospital - Sharma, Riya (Journal of Neonatal Surgery, 2025)
In the present research, which has been conducted in the Hanoi city of Vietnam, the secondary school students have been taken into consideration to find out the gender wise and ownership wise differences in their achievement in social science. For this, a sample of 100 students has been taken from 8 (4 public and 4 private) secondary schools. Among them, a sample of 50 students was selected from public and 50 from private secondary schools. From the 50 public secondary school students, 21 students were male and 29 were females. Whereas out of 50 private secondary school students 30 students were male and 20 female. The study reveals that the social science achievement of the students gets affected by the gender and not by the ownership of the schools.